Tinjauan Yuridis Perusahaan Pailit yang Berdampak pada Hak- Hak Karyawan - Muhammad Hilmi Shofwan Ali (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2025)
The main issue in this study is the legal uncertainty regarding the protection of employees’ rights when a company is declared bankrupt. In practice, employees often occupy a weak position due to overlapping provisions between bankruptcy law and labor law, which results in unpaid wages and severance pay. This situation creates serious problems since employees are highly dependent on the company’s continuity for their livelihood. This research employs a normative juridical method with statutory and case approaches. The proposed solution is the need for synchronization between the Bankruptcy Law and the Manpower Law, as well as strengthening the legal position of employees as preferred creditors during the curatorial process. Furthermore, improvement of enforcement mechanisms is necessary to ensure that court rulings can provide stronger guarantees for employees’ rights. The findings reveal that although employees are normatively granted preferential rights, practical obstacles still exist, including conflicts of interest among creditors, limited company assets, and the weak role of curators in safeguarding employees’ entitlements. In conclusion, legal protection of employees’ rights in bankrupt companies has not been fully effective. Therefore, regulatory harmonization and the strengthening of legal instruments are required to ensure certainty and fairness.